(untitled) (REMUNOM, 2026)
Oral health in children with Autism Spectrum Disorder (ASD) presents a significant challenge for their caregivers and healthcare professionals due to the behavioral and sensory characteristics of the disorder, which can make it difficult to implement an adequate oral hygiene routine. To identify the challenges for caregivers in supporting the oral health of children with Autism Spectrum Disorder (ASD) enrolled in municipal early childhood education centers in a northeastern brazilian capital. This descriptive study was developed using a mixed-methods approach (qualitative and quantitative), with a total of 45 caregivers interviewed. These caregivers were responsible for children with ASD, aged 2 to 6 years, enrolled in three early childhood education centers (CMEIs) in a northeastern brazilian capital. Data collection took place at the institutions, through semi-structured questionnaires administered in person, addressing sociodemographic data, oral hygiene habits, and perceptions about barriers to care. Respondents indicated that children’s resistance to brushing their teeth, the emotional burden on caregivers, and the difficulty in finding professionals who know how to work with children with ASD are among the main challenges. Reports also highlight feelings of insecurity and lack of support in dealing with crisis situations during oral hygiene routines. The difficulties reported go beyond the technical aspects of hygiene, involving emotional and institutional factors. This research may support inclusive practices and public policies, improving the quality of life for children with ASD and their families.